Myths and Misunderstandings About Child Sexual Abuse in Criminal Investigations - Denne, Emily (Journal of interpersonal violence, 2023)
Researchers have established that rape myths shape perceptions of victims and perpetrators in criminal cases. Researchers have devoted less attention to exploring the impact of child sexual abuse (CSA) myths in court. While we know that jurors believe myths and misconceptions about the nature of CSA, no work has explored how these myths appear during the prosecution of CSA cases. The purpose of the present investigation was to assess how defense attorneys apply myths more specific to CSA in the questioning of children testifying about alleged CSA. The present study compliments and expands upon a previous study by St. George and colleagues (2021a), where authors examined the use of rape myths in the questioning of children making allegations of CSA. In the current study, we examined testimonies of 122 children testifying in criminal cases of alleged CSA in the United States. We qualitatively coded 6,384 lines of questioning for references to CSA-focused myths related to the disclosure process, witnesses and privacy issues, assumptions of harm, and the child’s positive relationship with the perpetrator. These myths were common, occurring in over 10% of defense attorneys’ lines of questioning. Disclosure issues were the most frequent, followed by witness and privacy issues, assumptions of harm, and the child’s positive relationship with their perpetrator. In many cases, attorneys employed different strategies across child’s age to highlight these myths. These findings compliment those of prior work suggesting that CSA myths, much like rape myths, are appearing with regularity. Defense attorneys are likely capitalizing on jurors’ misconceptions to undermine children’s believability.